Assessment of the ICT Integration in Teaching Math and Science in High School: Basis for an ICT Integration Program - Arrieta, Gilbert Santos (Jurnal Pendidikan MIPA, 2020)
This descriptive study assessed the information and communications technology (ICT) integration in teaching Math and Science, and identified issues affecting technology integration. Nine Math teachers, and eight Science teachers was chosen as participant in this study. A survey instrument with Likert-five point scale was developed to explore participants’ perceptions towards ICT integration in teaching math and science in high school. The results showed that the status of technology integration in Math and Science is well-implemented. However, teachers needed time to plan and prepare technology-based instructional materials and update their skills in technology and pedagogy. They also needed to be supervised closely through feedback and mentoring. In terms of professional advancement, they needed to be updated and trained on curriculum development, pedagogy, and technology. Equipment and facilities needed to be increased, improved, and maintained, most especially the internet connection. It can be concluded that curriculum and instruction including faculty are greatly dependent on supervision, professional development, and equipment and facilities. The aforementioned three areas are well-implemented which made curriculum and instruction, and faculty extensively implemented. Keywords: ICT integration program, teaching math and science, high school. DOI: http://dx.doi.org/10.23960/jpmipa/v21i1.pp95-108